The world of Ion of Chios - Jennings, Victoria, 1970-; Katsaros, Andrea. (Mnemosyne, Supplements, 2007)
Sixteen international contributors investigate the life, works and reception of Ion of Chios (490/80-420s BC), the prolific Greek writer famed in antiquity for his polyeideia. His extraordinary range of writings in prose and poetry across multiple genres include tragedy, elegy, history, biography, mythography and philosophy. Ion is important to any study of Classical Greece because of the literary innovations which he pioneered. He is significant to the history of Athens and Chios as a contemporary of and commentator on Aeschylus, Cimon, Sophocles, Pericles, Themistocles and Socrates. This book is the first to examine how this fascinating but neglected man interacted with his peers and conceptualized himself and his world during one of the most exciting periods of ancient history.